INCREASING THE UNDERSTANDING OF THE CONCEPT OF NUMBERS THROUGH ANGKLUNG PLAYING (ACTION RESEARCH IN GROUP B IN PAUD ALFANI ￼￼￼￼￼2016/2017 ACADEMIC YEAR) - Dini Nurmalina Firsty; Myrnawati C.H; Hapidin . (Universitas Muhammadiyah Ponorogo, 2018)
The purpose of this study is to describe the process and results of angklung play activities to improve understanding of the concept of children under five in early childhood and whether angklung play can improve understanding of the concept of children in early childhood in 2017. Respondents in this study were 18 children from the group B PAUD Alfani in2017. The research method used is a model of Kemmis Taggart spiral action research consisting of: (a) planning, (b) action and observation, and (c) reflection. Instruments used in this study are field notes, interviews, and documentation. Scores of understanding data on economic concepts in children are analyzed quantitatively and qualitatively. The result of the data shows that the concept of learning in children increases from pre-cycle to first cycle and second cycle. Based on the observation of the action that has been done on the data given at the incidence rate 40.09%, and in the first cycle to 59.41% and then increased in the second cycle of 85.61%. The results of this study are (1) angklung playing activities can improve concept understanding in children group B PAUD Alfani in 2017, (2) concept comprehension score in children group B PAUD Alfani year 2017 increase from pre cycle to first cycle and first cycle to second cycle .